Abundant hydrogen production over well dispersed nickel nanoparticles confined in mesoporous metal oxides in partial oxidation of methane. (15th November 2019) - Ding, Chuanmin; Wang, Junwen; Guo, Songsong; Ma, Zili; Li, Yufeng; Ma, Lichao; Zhang, Kan
Abstract: To improve the stability of Ni catalysts and employ reactive oxygen species in reducible metal oxides, the Ni nanoparticles were confined within mesoporous metal oxides (La2 O3, Yb2 O3, ZrO2, CeO2 ) via evaporation-induced self assembly technique utilizing 3D honeycomb-like silica as substrate for partial oxidation of methane (POM). Compared with supported catalysts, the prepared catalysts showed superior catalysts stability especially 3D honeycomb-like ZrO2 and CeO2 supported Ni catalysts (Ni/3HL-ZrO2 -SiO2 and Ni/3HL-CeO2 -SiO2 ) due to confinement effect and strong interaction between Ni and metal oxides. CH4 conversion reached 90%–92%. Outstanding catalytic activity was attributed to highly dispersity of active metal. More importantly, abundant hydrogen production was observed over mesoporous CeO2, ZrO2 supported catalysts and the ratio of H2 /CO changed from nominal value 2 to 3. DFT theoretical calculations illuminated structural defect sites of reducible support like CeO2, ZrO2 afforded generation of surface hydroxyl group, which can be regenerated by activation of water and reoxidation of CeO2, ZrO2 . Hydroxyl group was beneficial to accelerate greatly water gas shift reaction, promoting the production of hydrogen. This may provide a strategy to regulate production composition of POM to expand its downstream process. Graphical abstract: The hydroxyl groups within mesoporous metal oxide accelerated WGS reaction adjusting the product composition of POM. Image 1 Highlights: The Ni nanoparticles were confined within mesoporous metal oxide. The confinement contributed to anti-sintering and coking ability of Ni catalyst. The mesoporous metal oxides promoted generation of surface hydroxyl groups. Hydroxyl groups accelerated WGS reaction and regulated production composition.